Features of Silver Carp (Hypophthalmichthys molitrix) Sperm Collecting for Cryopreservation Following Hormonal Stimulation - Butskyi, Kyrylo I.; Puhovkin, Anton Yu. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 162